The Not-So Rosy Periwinkle: Political Dimensions of Medicinal Plant Research - Harper, Janice (Ethnobotany Research and Applications, 2005)
As pharmaceutical companies and conservation groups increasingly recognize the biomedical and economic potential of indigenous medicines from tropical rainforests, romanticized stereotypes of rainforest medicines as inherently beneficial abound. These ideas fail to take into consideration the question of why those living in the rainforest need medicines, and whether or not “traditional” medicines are a “choice” to those who do not have access to pharmaceutical medicines. This paper presents a theoretical analysis of how the study and practice of commodifying indigenous medicines has tended to exclude the structural factors shaping their use in indigenous communities, drawing on 14 months’ ethnographic research on access to medicines near the Ranomafana National Park in southeastern Madagascar. I suggest that researchers and practitioners of conservation and development consider the ways in which “modernizing” tropical rainforest communities shapes patterns of health and illness unevenly, thereby contributing to changing medical “traditions.”